Fast comparisons of circuit implementations. - Karandikar, S.K (IEEE Transactions on VLSI systems)
Digital designs can be mapped to different implementations using diverse approaches, with varying cost criteria. Post-processing transforms, such as transistor sizing, can significantly improve circuit performance by optimizing critical paths to meet timing specifications. However, most transistor sizing tools have high execution times, and the possible delay gains due to sizing, and the associated costs are not known prior to sizing. In this paper, we present two metrics for comparing different implementations-the minimum achievable delay and the cost of achieving a target delay-and show how these can be estimated without running a sizing tool. Using these fast and accurate performance estimators, a designer can determine the tradeoffs between multiple functionally identical implementations, and size only the selected implementation.